Baroreflex activation therapy for the treatment of heart failure with a reduced ejection fraction: safety and efficacy in patients with and without cardiac resynchronization therapy. (10th June 2015) - Zile, Michael R.; Abraham, William T.; Weaver, Fred A.; Butter, Christian; Ducharme, Anique; Halbach, Marcel; Klug, Didier; Lovett, Eric G.; Müller‐Ehmsen, Jochen; Schafer, Jill E.; Senni, Michele; Swarup, Vijay; et al.
Abstract : Aims: Increased sympathetic and decreased parasympathetic activity contribute to heart failure (HF) symptoms and disease progression. Carotid baroreceptor stimulation (baroreflex activation therapy, BAT) results in centrally mediated reduction of sympathetic and increase in parasympathetic activity. Because patients treated with cardiac resynchronization therapy (CRT) may have less sympathetic/parasympathetic imbalance, we hypothesized that there would be differences in the response to BAT in patients with CRT vs. those without CRT. Methods and results: New York Heart Association (NYHA) Class III patients with an ejection fraction (EF) ≤35% were randomized (1 : 1) to ongoing guideline‐directed medical and device therapy (GDMT, control) or ongoing GDMT plus BAT. Safety endpoint was system‐/procedure‐related major adverse neurological and cardiovascular events (MANCE). Efficacy endpoints were Minnesota Living with Heart Failure Quality of Life (QoL), 6‐min hall walk distance (6MHWD), N ‐terminal pro‐brain natriuretic peptide (NT‐proBNP), left ventricular ejection fraction (LVEF), and HF hospitalization rate. In this sample, 146 patients were randomized (70 control; 76 BAT) and were 140 activated (45 with CRT and 95 without CRT). MANCE‐free rate at 6 months was 100% in CRT and 96% in no‐CRT group. At 6 months, in the no‐CRT group, QoL score, 6MHWD, LVEF, NT‐proBNP and HF hospitalizations were significantly improved in BAT patients compared with controls. Changes in efficacy endpoints in the CRT group favoured BAT; however, the improvements were less than in the no‐CRT group and were not statistically different from control. Conclusions: BAT is safe and significantly improved QoL, exercise capacity, NTpro‐BNP, EF, and rate of HF hospitalizations in GDMT‐treated NYHA Class III HF patients. These effects were most pronounced in patients not treated with CRT.